KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH (STUDI KASUS NASABAH BANK BRI DI GORONTALO) - Siti Rahmatia P.Z Saputra; Meriani Angguda; Nabila Azhara (Universitas Veteran Bangun Nusantara, 2022)
This research was conducted to determine how much influence service quality and customer satisfaction have on Bank BRI Gorontalo branch. The purpose of this study was to determine the effect of service quality on customer satisfaction at BRI bank in Gorontalo. In this study, we took samples from customers who use BRI bank in Gorontalo. The method in this study is a quantitative method and data collection using a questionnaire. The population in this study were all Gorontalo people as customers at BRI Bank in Gorontalo, 100 respondents were sampled. The results of the study prove that the magnitude of the influence of service quality on customer satisfaction and there is no influence of customer satisfaction on service quality.